THE IMPLEMENTATION OF KAIZEN METHOD IN IMPROVING EFL STUDENTS’ SPEAKING SKILL - Kelvin Wildasyah; Dyah Kurniawati; Dholiful Hadi (Pro-ELLitera, 2024)
The purpose of this study is to investigate toward the implementation of the Kaizen method on developing speaking skills in students of various educational levels and to investigate their responses. The study included a group of nine students called the Kaizen Group. To provide a thorough analysis of the impact of the Kaizen technique on speaking skill, the research design included descriptive qualitative research. The Kaizen Group was exposed to the Kaizen method. The data analysis was descriptive which gathered from pre-test, 3 days treatment, and post-tests. Observations, and feedback surveys were used to collect data. According to the research findings, students in the Kaizen Group improved positively in their speaking skills after using the Kaizen method. The Kaizen approach's gradual and continuous nature helped students to gain confidence and achieve greater fluency and accuracy in their spoken English. Overall, this study reveals the usefulness of the Kaizen method in improving speaking skills at various educational levels. The Kaizen Group's positive achievements imply that adopting the Kaizen philosophy into language teaching can be a helpful technique for fostering language competency and encouraging ongoing growth in students' speaking abilities.